Pension Systems in the EU — Some Policy Issues - Mikkel Barslund (Intereconomics)
Abstract To what extent a pension system can be judged fair given structural differences in life expectancy across socioeconomic groups is not straightforward and will depend on the exact design of the system and other social policies in place, and how these policies interact with the pension system.